Sample integrity evaluation and EPA method 325B interlaboratory comparison for select volatile organic compounds collected diffusively on Carbopack X sorbent tubes. (August 2017) - Oliver, Karen D.; Cousett, Tamira A.; Whitaker, Donald A.; Smith, Luther A.; Mukerjee, Shaibal; Stallings, Casson; Thoma, Eben D.; Alston, Lillian; Colon, Maribel; Wu, Tai; Henkle, Stacy
Abstract: A sample integrity evaluation and an interlaboratory comparison were conducted in application of U.S. Environmental Protection Agency (EPA) Methods 325A and 325B for diffusively monitoring benzene and other selected volatile organic compounds (VOCs) using Carbopack X sorbent tubes. To evaluate sample integrity, VOC samples were refrigerated for up to 240 days and analyzed using thermal desorption/gas chromatography-mass spectrometry at the EPA Office of Research and Development laboratory in Research Triangle Park, NC, USA. For the interlaboratory comparison, three commercial analytical laboratories were asked to follow Method 325B when analyzing samples of VOCs that were collected in field and laboratory settings for EPA studies. Overall results indicate that the selected VOCs collected diffusively on sorbent tubes generally were stable for 6 months or longer when samples were refrigerated. This suggests the specified maximum 30-day storage time of VOCs collected diffusively on Carbopack X passive samplers and analyzed using Method 325B might be able to be relaxed. Interlaboratory comparison results were in agreement for the challenge samples collected diffusively in an exposure chamber in the laboratory, with most measurements within ±25% of the theoretical concentration. Statistically significant differences among laboratories for ambient challenge samples were small, less than 1 part per billion by volume (ppbv). Results from all laboratories exhibited good precision and generally agreed well with each other. Highlights: VOCs collected on Carbopack X tubes were stable for 6 months when refrigerated. Four laboratories followed EPA Method 325B to analyze ambient and spiked samples. The four laboratories used varying standards preparation and loading techniques. Laboratory results generally agreed to within ±25% of theoretical concentrations. Results suggest Method 325B can be reliably employed by commercial laboratories.